Synthesis, reactivity, and electrochemical studies of gold(I) and gold(III) complexes supported by N-heterocyclic carbenes and their application in catalysis - Pažický, Marek; Loos, Annette; Ferreira, Maria João Gomes; Serra, Daniel; Vinokurov, Nikolai; Rominger, Frank; Jäkel, Christoph; Hashmi, A. Stephen K.; Limbach, Michael (Organometallics, 2010)
In the present study we describe the efficient synthesis of various Au(I) complexes supported by NHC ligands. Some of these ligands have a pendant pyridine arm that is linked with various tethers (CH2)n to the NHC backbone (n = 0−2). The chloride in the Au(I) complexes is easily and cleanly replaced by an aryl group upon reaction with an aryl-Grignard reagent. The thus obtained aryl Au(I) complexes are cleanly oxidized to the corresponding Au(III) complexes with phenyliodoso dichloride, as are the corresponding halide Au(I) complexes. The attempted salt metathesis with the parent Au(III) complex led to the oxidative coupling of the aryl residues with formation of the Au(I) complex. Some of the complexes are promising catalysts in the cycloisomerization of an ω-alkynylfuran to isobenzofuranol in the presence of a silver salt. For those precursors with pendant pyridine arms, a cationic dimeric Au complex was isolated and characterized, which represents a catalyst resting state and forms under reaction conditions.